Reaction of imidazoline-2-selone derivatives with mesityltellurenyl iodide: a unique example of a 3c-4e Se→Te←Se three-body system embedding a tellurenyl cation. (20th June 2019) - Aragoni, M. Carla; Arca, Massimiliano; Blake, Alexander J.; Cadoni, Enzo; Copolovici, Lucian O.; Isaia, Francesco; Lippolis, Vito; Murgia, Sergio; Pop, Alexandra M.; Silvestru, Cristian; Tidey, Jeremiah P.; Varga, Richard A.
Abstract : 1, 2-Bis(3-methyl-4-imidazolin-2-selone)ethane was used to stabilize the first example of an authentic mesityltellurenyl cation, [MesTe] +, as a charge transfer adduct featuring a 3c-4e Se→Te←Se three-body system. Abstract : The reactions of 1, 1′-bis(3-methyl-4-imidazolin-2-selone)methane (L 1 ) and 1, 2-bis(3-methyl-4-imidazolin-2-selone)ethane (L 2 ) with mesityltellurenyl iodide (MesTeI) [Mes = 2, 4, 6-Me3 C6 H2 ] yielded the neutral [L 1 ·2MesTeI]·2CH2 Cl2 and the ionic [L 2 ·MesTe]2 (MesTeI2 )2 compounds, respectively, which were characterized by X-ray diffraction analysis. DFT (mPW1PW//LANL08d/def2-SVP) and NBO calculations, supported by structural and FT-Raman measurements, show that the latter compound represents the first example of an authentic mesityltellurenyl cation, [MesTe] +, stabilized within a [MesTe(B)2 ] + (B = Lewis base) charge transfer adduct featuring a 3c-4e Se→Te←Se three-body system.